The Online Learning Transition: Challenges and Opportunities - Taufiq Satria Mukti; Sharfina Nur Amalina (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Corona Virus Disease 2019 is currently still volatile. Large-scale restrictions stop activities outside the home that have a broad impact on life, including the field of education. Learning activities transition into online learning at home. Changes due to this condition pose challenges as well as opportunities for students and educators. The purpose of this study is to explore information on challenges and opportunities in online learning so that the results of this study can provide policy recommendations in the implementation of learning in the following semester. This survey research was conducted by distributing questionnaires (google forms) related to the challenges and learning opportunities for the second-semester students of the 2019 batch of Maulana Malik Ibrahim State Islamic University Malang. The results obtained indicate that elements of student dissatisfaction dominate each aspect of the majority during online learning. The conclusion obtained from this research is that online learning has obstacles to be transformed into opportunities as an alternative problem solving to the stability of the quality of Education.